Specific use of heimath by the pilots of the Grand DuchE of Finland in the 19th Century (Revista de Investigaciones Universidad del Quindío, 2022)
The article presents the historical and legal study results concerning the specifics of heimath use by the pilots of the Grand Duchy of Finland. To do so, general scientific (dialectical, comparative, historical-genetic, structural-functional), as well as specific scientific (specific-sociological, formal-logical, historical-legal, comparative jurisprudence) methods are utilized. It has been established that a heimath as an additional financial guarantee for the well-being of pilots in the Grand Duchy of Finland came into the Finnish legislation from the Swedish tradition. Pilots, being personally free people, used this form of land tenure as civil servants or as private property. At the same time, differences in the rights of each individual heimath were revealed in terms of its importance, profitability, size, remoteness, as well as in terms of personal qualities and the pilot service position who received it.
Keywords: Heimath; Grand Duchy; financial guarantees; self-government; private property right